Effects of environmental change and early-life stochasticity on Pacific bluefin tuna population growth. (August 2019) - Ijima, Hirotaka; Jusup, Marko; Takada, Takenori; Akita, Tetsuya; Matsuda, Hiroyuki; Klanjscek, Tin
Abstract: Species conservation and fisheries management require approaches that relate environmental conditions to population-level dynamics, especially because environmental conditions shift due to climate change. We combined an individual-level physiological model and a conceptually simple matrix population model to develop a novel tool that relates environmental change to population dynamics, and used this tool to analyze effects of environmental changes and early-life stochasticity on Pacific bluefin tuna (PBT) population growth. We found that (i) currently, PBT population experiences a positive growth rate, (ii) somewhat surprisingly, stochasticity in early life survival increases this growth rate, (iii) sexual maturation age strongly depends on food and temperature, (iv) current fishing pressure, though high, is tolerable as long as the environment is such that PBT mature in less than 9 years of age (maturation age of up to 10 is possible in some environments), (v) PBT population growth rate is much more susceptible to changes in juvenile survival than changes in total reproductive output or adult survival. These results suggest that, to be effective, fishing regulations need to (i) focus on smaller tuna (i.e., juveniles and young adults), and (ii) mitigate adverse effects of climate change by taking into the account how future environments may affect the population growth. Highlights: We developed a novel tool that relates environmental change to population dynamics. We used the new tool to analyze Pacific bluefin tuna (PBT) population growth. We found that PBT population experiences a positive growth rate. Surprisingly, stochasticity in early life survival speeds up population growth. PBT fishing is tolerable if environment supports fast enough maturation ( < 9 y/o).